The Impact of the COVID-19 Pandemic on People With Epilepsy. An Italian Survey and a Global Perspective - Mostacci, Barbara; Licchetta, Laura; Cacciavillani, Carlotta; Di Vito, Lidia; Ferri, Lorenzo; Menghi, Veronica; Stipa, Carlotta; Avoni, Patrizia; Provini, Federica; Muccioli, Lorenzo; Vignatelli, Luca; Mazzoni, Stefania; et al. (Frontiers in Neurology, 2020)
Objectives: We explored the impact of the coronavirus disease-19 (COVID-19) emergency on the health of people with epilepsy (PwE). We also investigated their attitude towards telemedicine. Methods: The PubMed database up to September 10, 2020 was searched for questionnaire-based studies conducted in PwE during the COVID-19 emergency, and the literature retrieved was reviewed. In addition, all patients who had a telephone consultation with our center between May 7 and July 31, 2020 were invited to fill in a 57-item online questionnaire focusing on epilepsy and comorbidities, any changes in lifestyle or clinical conditions and any emergency-related problems arising during the COVID-19 emergency, and their views on telemedicine. Associations between variables were detected through X2 test and Fisher’s exact test. Univariate and multivariate logistic regression models were used to evaluate the effects of different factors on clinical conditions. Results: Twelve studies met the literature search criteria. They showed that the rate of seizure worsening during the emergency ranged from 4 to 35% and was mainly correlated with epilepsy severity, sleep disturbances and COVID-19-related issues. Our questionnaire was filled in by 222 PwE or caregivers. One hundred (76.6%) reported unchanged clinical conditions, 25 (11.3%) an improvement, and 27 (12%) a deterioration. Reported clinical worsening was associated with a psychiatric condition and/or medication (OR=12.59, p<0.001), sleep disorders (OR=8.41, p=0.001), limited access to healthcare (OR=4.71, p=0.016), and experiencing seizures during the emergency (OR=4.51, p=0.007). Telemedicine was considered acceptable by 116 subjects (52.3%). Conclusions: Most PwE did not experience a significant change in their clinical conditions during the COVID-19 emergency. However, severity of epilepsy, concomitant disability, comorbid psychiatric conditions, sleep